MENGGUGAT DOMINASI POSITIVISME HUKUM - Faisal Faisal (Doctoral of Law Program, Faculty of Law, Universitas Diponegoro, 2009)
The development of legal positivism cannot be separated from the Cartesian–Newtonian paradigm introduced by René Descartes and Isaac Newton. This paradigm has significantly contributed to the advancement of science and technology, thereby improving human civilization. However, its emphasis on objectivity, determinism, materialism, scientism, reductionism, instrumentalism, dualism, and mechanistic reasoning has also reduced the complexity of human and social realities. Within this framework, society is perceived as a mechanical system governed by fixed and predictable laws. Such assumptions have profoundly influenced the emergence and consolidation of legal positivism, which conceives law as a closed, objective, and value-neutral system detached from morality and social context. This article argues that the dominance of the Cartesian–Newtonian worldview has shaped the epistemological foundations of modern legal science while simultaneously limiting the capacity of law to respond to social justice and the dynamic nature of human life. Consequently, a critical reorientation toward more contextual and humanistic legal paradigms, such as progressive law, is required to overcome the limitations of legal positivism.